2014
DOI: 10.1002/art.38729
|View full text |Cite
|
Sign up to set email alerts
|

Osteophytes, Enthesophytes, and High Bone Mass: A Bone‐Forming Triad With Potential Relevance in Osteoarthritis

Abstract: ObjectivePrevious studies of skeletal remains have suggested that both enthesophytes and osteophytes are manifestations of an underlying bone-forming tendency. A greater prevalence of osteophytes has been observed among individuals with high bone mass (HBM) compared with controls. This study was undertaken to examine the possible interrelationships between bone mass, enthesophytes, and osteophytes in a population of individuals with extreme HBM.MethodsCases of HBM (defined according to bone mineral density [BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…This is supported by the additional observation that HBM individuals also have a greater prevalence and severity of radiographic pelvic enthesophytes (bony spurs at tendon and ligament insertions). 61 Although the genetic basis for increased BMD in the majority of these HBM cases remains to be determined, and is the subject of ongoing studies, a genome-wide association analysis has shown overrepresentation of single-nucleotide polymorphisms (SNPs) that were previously shown to be associated with BMD variation in the general population. 62 It is hoped that whole-exome sequencing in this unique group, currently underway, could identify novel pathways with a role in both OA and bone mass regulation.…”
Section: Oa In High Bone Mass Individuals: a Novel Approachmentioning
confidence: 99%
“…This is supported by the additional observation that HBM individuals also have a greater prevalence and severity of radiographic pelvic enthesophytes (bony spurs at tendon and ligament insertions). 61 Although the genetic basis for increased BMD in the majority of these HBM cases remains to be determined, and is the subject of ongoing studies, a genome-wide association analysis has shown overrepresentation of single-nucleotide polymorphisms (SNPs) that were previously shown to be associated with BMD variation in the general population. 62 It is hoped that whole-exome sequencing in this unique group, currently underway, could identify novel pathways with a role in both OA and bone mass regulation.…”
Section: Oa In High Bone Mass Individuals: a Novel Approachmentioning
confidence: 99%
“…These osteoarthritis hips exerted a bony phenotype with increased osteophytes and bone sclerosis. This study [10] suggests that this population with a 'bone-forming' tendency are at higher risk of developing osteoarthritis. Conversely, results from the Rotterdam Study suggest that a subtype of patients with an atrophic osteoarthritis phenotype (as defined by absence of osteophyte) are at higher risk of hip fracture, independently from systemic BMD [11].…”
Section: Bone Mineral Densitymentioning
confidence: 85%
“…Further characterisation of knee OA revealed a similar, osteophyte predominant, radiographic OA phenotype [10]. Additional evidence of a ‘bone-forming’ tendency is supported by a greater prevalence and severity of radiographic pelvic enthesophytes (bony spurs at tendon/ligament insertions) seen in HBM individuals, compared with family controls [11].…”
Section: Introductionmentioning
confidence: 86%